The Power of Questioning: Teacher’s Questioning Strategies in the EFL Classrooms - ANISSA ASTRID; RIZQY DWI AMRINA; DETA DESVITASARI; UCI FITRIANI; AISYAH SHAHAB (Indonesian Research Journal in Education |IRJE|, 2019)
The aims of the study were to investigate English teachers’ questioning strategies at one Madrasah in Palembang, South Sumatera. The qualitative research method with a case study approach was employed to look at the ways of the English teachers’ questioning strategies in the processes of teaching and learning and the reasons that made them use certain questioning strategies. The participants in this study were English teachers. We used observation and interviews as our data collection techniques. The observation was used to look at the teacher’s questioning types used in the daily practices of teaching in the EFL classroom while the interview was used to understand the reasons that made them use those types of questioning strategies. Our findings showed three types of teacher’s questioning strategies used by teachers in their teaching and learning processes including convergent, divergent, and procedural questions. Teachers mostly used convergent questions (yes/no and short answers). We also found five reasons why teachers preferred to those types of questioning strategies including recalling students’ understanding, attracting students’ attention, increasing students’ thinking in higher order level, and engaging students in learning activities. Implications and recommendations are also discussed.